2021
DOI: 10.1116/6.0000682
|View full text |Cite
|
Sign up to set email alerts
|

Practical guides for x-ray photoelectron spectroscopy (XPS): Interpreting the carbon 1s spectrum

Abstract: The carbon 1s photoelectron spectrum is the most widely fit and analyzed narrow scan in the x-ray photoelectron spectroscopy (XPS) literature. It is, therefore, critically important to adopt well-established protocols based on best practices for its analysis, since results of these efforts affect research outcomes in a wide range of different application areas across materials science. Unfortunately, much XPS peak fitting in the scientific literature is inaccurate. In this guide, we describe and explain the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
182
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(194 citation statements)
references
References 56 publications
12
182
0
Order By: Relevance
“…This paper will not consider the fitting of adventitious or polymeric carbon species but will focus on predominantly graphitic and diamond-like materials. For discussion on the former, the reader is directed to [11].…”
Section: The C (1s) Spectrum Of Diamond Hopg and Graphitic Carbonsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper will not consider the fitting of adventitious or polymeric carbon species but will focus on predominantly graphitic and diamond-like materials. For discussion on the former, the reader is directed to [11].…”
Section: The C (1s) Spectrum Of Diamond Hopg and Graphitic Carbonsmentioning
confidence: 99%
“…The fitting of the graphitic C (1s) envelope is one of the most common errors encountered in the literature [15], and the asymmetric shape is something commonly ignored in The fitting of the graphitic C (1s) envelope is one of the most common errors encountered in the literature [15], and the asymmetric shape is something commonly ignored in may published papers. Recently, Linford et al [11] reported a method for fitting the C (1s) envelope of graphitic carbon materials, using a reference spectrum of clean graphite/HOPG as a model for the graphitic backbone. This method is useful and is indeed a method the current author has used for many years.…”
Section: The C (1s) Spectrum Of Diamond Hopg and Graphitic Carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is analogous to the "disproof by counterexample" method used by mathematicians in which a single counterexample is used to disprove a proposition. [29] In other words, one might question the validity of a fitting protocol if different starting conditions in it lead to significantly different results. The method developed in this work tests for local minima in a fit space.…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in C 1s narrow scans is a result of a recent report that showed that they are the most frequently presented and researched narrow scans in the scientific literature, [18] and that they are often fit incorrectly. [29,30] Calculations for the four-component peak fits. We first created a 32 x 4 matrix of random numbers uniformly distributed between 0 and 1 using the following MATLAB script: >> rng shuffle >> x = rand (64,4) This algorithm for generating random numbers, D.E.…”
Section: Introductionmentioning
confidence: 99%